A Review of Rural Development program in India: Exploring the Impact of the Mahatma Gandhi National Rural Employment Guarantee Act on Rural Development and Poverty Alleviation in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
When we talk about rural development, we're talking about making things better for those wholive in remote, sparsely populated places. Said to be a Silver Bullet, the Mahatma Gandhi National RuralEmployment Guarantee Act (MGNREGA) poverty and unemployment in rural areas by creating a need for amore productive workforce in the villages. It the provision of a different means of subsistence has theeffect of decreasing migration and restricting child labor, reducing poverty, and establishing selfsustainingcommunities by creating productive assets such For which it has been used in theconstruction of roads, the cleaning of water tanks, soil and water conservation efforts, etc.Considered tobe the world's greatest anti-poverty initiative. In this paper discuss the , components of ruraldevelopment, fundamental aspects of rural development, role of education in rural development, need ofeducation for rural development, the right to education (RTE).